Jurisdiction in an immigrant-settler society: the "Jewish and democratic state" - Kimmerling, Baruch (2002)
The major dilemma presented in this article is how a state that officially and constitutionally defines itself as "Jewish and democratic" relates to two categories of Arab minorities: (a) the Arab citizens of Israel and (b) the Palestinians who have resided in the occupied territories since the 1967 war. The analysis will focus on both the legislative and judicial levels, as they reflect the Israeli state's policy toward minority groups more than any other sphere. The article examines the Israeli state's delineation of various boundaries in various contexts, allows the state to exhibit a "democratic facade", and legitimizes the regime and the state. The Palestinian population in the occupied territories is, even today, after establishment of an autonomous national authority )following a partial implementation of the Oslo Accords), still included within the control and economic system of the Israeli state. - Reproduced. The major dilemma presented in this article is how a state that officially and constitutionally defines itself as "Jewish and democratic" relates to two categories of Arab minorities: (a) the Arab citizens of Israel and (b) the Palestinians who have resided in the occupied territories since the 1967 war. The analysis will focus on both the legislative and judicial levels, as they reflect the Israeli state's policy toward minority groups more than any other sphere. The article examines the Israeli state's delineation of various boundaries in various contexts, allows the state to exhibit a "democratic facade", and legitimizes the regime and the state. The Palestinian population in the occupied territories is
Keywords: Politics and government